You can't come back - Lee, Cheryl Xin Ying (2019)
You Can’t Come Back is a comedy film produced by Comic Sans Productions, as part of an undergraduate Final Year Project (FYP) in the Wee Kim Wee School of Communication and Information (WKWSCI), Nanyang Technological University (NTU). The short film was produced by Cheryl Lee Xin Ying, Guan Yue (Francis), Shermane Wong and Tay Jun Wen, under the supervision of Mr. Daniel Heng.